2017
DOI: 10.1186/s13034-017-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of attention deficit hyperactivity disorder (ADHD) among Ugandan children; a cross-sectional study

Abstract: BackgroundAttention deficit hyperactivity disorder (ADHD) is a common neuropsychiatric disorder among the children. The burden of ADHD or its associated factors in Uganda are not known. The objective of this study was to determine the prevalence and the associated factors of ADHD among children attending the neurology and psychiatry clinics at Mulago National Referral Hospital.MethodsUsing the disruptive behavior scale (45 items), we investigated the presence of ADHD symptoms among children attending Mulago Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
4
19
1
Order By: Relevance
“…The sample size of the included studies ranged from 100 to 1477. Ten studies were good in quality, one moderate (31), and one poor (34).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size of the included studies ranged from 100 to 1477. Ten studies were good in quality, one moderate (31), and one poor (34).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The characteristics of these studies are summarized in Table 1. Selected studies were conducted in Nigeria [30][31][32], Sudan [33], Uganda [34], Congo [35], Kenya [36,37], Egypt [38][39][40][41], and Ethiopia [42]. Age at diagnosis of ADHD varies from 4 to 18 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies conducted in Uganda have focused on ADHD and been carried out in health facilities. For example, Wamulugwa et al reported a prevalence rate of 11% and Mpango et al reported a prevalence rate of 6% for ADHD among children with psychiatric diagnoses and HIV-positive adolescents respectively in Uganda [15, 16]. Our study reported lower rates of ADHD (2.67%), which could be most likely due to the difference in study population.…”
Section: Discussionmentioning
confidence: 50%
“…Though the prevalence of behavioral problems varies across cultures in the sub-Saharan Africa, estimates indicate prevalence rates ranging from 12 to 33% [8, 13, 14]. Recent estimates from a specialized children’s clinic at Mulago National Referral Hospital in Uganda reported that 11% of the participants had attention deficit hyperactive disorder (ADHD) symptoms and 8.57% had conduct disorders [15]. In a related study, Mpango et al unraveled a prevalence rate for ADHD of 6% among children and adolescents with HIV/AIDS in specialized HIV/AIDS clinics in central and southwestern Uganda [16].…”
Section: Introductionmentioning
confidence: 99%